2008
DOI: 10.2165/00044011-200828060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioavailability of Lornoxicam as Single Doses of Quick-Release Tablet, Standard Tablet and Intramuscular Injection

Abstract: Lornoxicam-QR and lornoxicam-IM did not differ with respect to AUCinfinity, Cmax and tmax, but both lornoxicam-QR and lornoxicam-IM showed significantly shorter tmax and significantly higher Cmax values than lornoxicam-ST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
6
0
4
Order By: Relevance
“…Milder histopathological changes were observed on evaluating the toxic effects of the other drugs. Lornoxicam seems to be one of the drugs that can be intramuscularly used for acute pain treatment, and there are no reports on sciatic nerve damage induced by an intramuscular injection of this drug in the gluteal region or its histopathological effects on the sciatic nerve [24, 25]. Lornoxicam injection in the sciatic nerve resulted in greater damage supported based on the histopathological evidence, and anti-S100 positivity was detected to be lower in the lornoxicam group with injection in the sciatic nerve than in the control group with serum physiological injection in the sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Milder histopathological changes were observed on evaluating the toxic effects of the other drugs. Lornoxicam seems to be one of the drugs that can be intramuscularly used for acute pain treatment, and there are no reports on sciatic nerve damage induced by an intramuscular injection of this drug in the gluteal region or its histopathological effects on the sciatic nerve [24, 25]. Lornoxicam injection in the sciatic nerve resulted in greater damage supported based on the histopathological evidence, and anti-S100 positivity was detected to be lower in the lornoxicam group with injection in the sciatic nerve than in the control group with serum physiological injection in the sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2 respectively. Furthermore, the fact that, LOR being water insoluble drug 15,16 has high affinity towards the fatty bases than PEGs base 14 . This result also agrees with Abou-Taleb et al, 2006 who found that the release of rofecoxib, selective cox-II inhibitor, from PEGs bases was higher than those of fatty bases e.g., witepsol E-75 and suppocire AM and CM 4 .…”
Section: Physical Characteristics Of Lor Suppositoriesmentioning
confidence: 99%
“…Гепатотоксичность при использовании НПВС проявляется нечасто. В 1-4% случаев может наблюдаться бессимптомное умеренное повышение уровня печеночных ферментов [2,9,15,17].…”
Section: в практику педиатраunclassified
“…Так, ЦОГ-1 постоянно присутствует в тканях, и с ее участием образуются простагландины, выполняющие протективные функции в слизистой оболочке желудка, эндотелии, регулирующие почечный кровоток. С ингибированием ЦОГ-1 и снижением регулирующих физиологических эффектов ПГ связаны побочные действия НПВС [6,8,9]. ЦОГ-2 в норме обнаруживается в незначительных количествах.…”
unclassified